2021
DOI: 10.5694/mja2.51361
|View full text |Cite
|
Sign up to set email alerts
|

Competing risks of death and kidney failure in a cohort of Australian adults with severe chronic kidney disease

Abstract: Objectives To examine the competing risks of death (any cause) and of kidney failure in a cohort of Australian adults with severe chronic kidney disease. Design Population‐based cohort study; analysis of linked data from the Tasmanian Chronic Kidney Disease study (CKD.TASlink), 1 January 2004 – 31 December 2017. Participants All adults in Tasmania with incident stage 4 chronic kidney disease (estimated glomerular filtration rate [eGFR], 15‒29 mL/min/1.73 m2). Main outcome measures Death or kidney failure (defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Three of these studies 18,23,24 and the large validation study by Tangri et al 6, undertook recalibration for use in an external population 19,25,26 . Previous work has demonstrated differences in practice between Australia and Canada in regards to eGFR and commencement of dialysis 7,8 . To account for this we have analysed several alternative endpoints which have demonstrated similar findings for discrimination to demonstrate the robustness of our results.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Three of these studies 18,23,24 and the large validation study by Tangri et al 6, undertook recalibration for use in an external population 19,25,26 . Previous work has demonstrated differences in practice between Australia and Canada in regards to eGFR and commencement of dialysis 7,8 . To account for this we have analysed several alternative endpoints which have demonstrated similar findings for discrimination to demonstrate the robustness of our results.…”
Section: Discussionmentioning
confidence: 76%
“… 19 , 25 , 26 Previous work has demonstrated differences in practice between Australia and Canada in regards to eGFR and commencement of dialysis. 7 , 8 To account for this we have analysed several alternative endpoints which have demonstrated similar findings for discrimination to demonstrate the robustness of our results. For calibration, this has demonstrated that the observed and predicted risk are better aligned when using the outcome of <7.5 mL/min/1.73m 2 which further highlight the differences in dialysis initiation practices between systems.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Over the years, there has been greater appreciation of the epidemiology of CKD where it has become apparent to clinicians that the major competing risk for dialysis is death from CVD [ 65 , 66 ]. This has resulted in broadening the focus of CKD care to include CVD risk reduction, in addition to or concomitant with, reducing the progressive decline in kidney function.…”
Section: Discussionmentioning
confidence: 99%